Onychomycosis: An Updated Review - Leung, Alexander K.C.; Lam, Joseph M.; Leong, Kin F.; Hon, Kam L.; Barankin, Benjamin; Leung, Amy A.M.; Wong, Alex H.C. (Recent Patents on Inflammation & Allergy Drug Discovery, 2020)
Background: Onychomycosis is a common fungal infection of the nail. Objective: The study aimed to provide an update on the evaluation, diagnosis, and treatment of onychomycosis. Methods: A PubMed search was completed in Clinical Queries using the key term “onychomycosis”. The search was conducted in May 2019. The search strategy included meta-analyses, randomized controlled trials, clinical trials, observational studies, and reviews published within the past 20 years. The search was restricted to English literature. Patents were searched using the key term “onychomycosis” in www.freepatentsonline.com. Results: Onychomycosis is a fungal infection of the nail unit. Approximately 90% of toenail and 75% of fingernail onychomycosis are caused by dermatophytes, notably Trichophyton mentagrophytes and Trichophyton rubrum. Clinical manifestations include discoloration of the nail, subungual hyperkeratosis, onycholysis, and onychauxis. The diagnosis can be confirmed by direct microscopic examination with a potassium hydroxide wet-mount preparation, histopathologic examination of the trimmed affected nail plate with a periodic-acid-Schiff stain, fungal culture, or polymerase chain reaction assays. Laboratory confirmation of onychomycosis before beginning a treatment regimen should be considered. Currently, oral terbinafine is the treatment of choice, followed by oral itraconazole. In general, topical monotherapy can be considered for mild to moderate onychomycosis and is a therapeutic option when oral antifungal agents are contraindicated or cannot be tolerated. Recent patents related to the management of onychomycosis are also discussed. Conclusion: Oral antifungal therapies are effective, but significant adverse effects limit their use. Although topical antifungal therapies have minimal adverse events, they are less effective than oral antifungal therapies, due to poor nail penetration. Therefore, there is a need for exploring more effective and/or alternative treatment modalities for the treatment of onychomycosis which are safer and more effective.
Keywords: terbinafine